2019
DOI: 10.7307/ptt.v31i4.3088
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Applicable Adjacent Horizontal Curve Radii Using Operating Speed

Abstract: Design of curves and their adjacent elements presents the greatest safety problem on rural two-lane roads. The use of the existing alignment consistency safety criteria (design, operating speed, and driving dynamic consistency) could have some shortcomings, especially in countries where the project or design speed is in use instead of (higher) operating speed. The consequence is that the designer should use smaller cross fall on curves than needed, while the calculated side friction is lower than in reality. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A sharp horizontal curve leads to the maximum difference in operating speed if the AT speed is high. Radii of horizontal alignment less than 100 m have a significant influence on speed [47]. Furthermore, the driving workload is primarily generated during the maneuver stage, and a radius of horizontal alignment of less than 500 m imposes an additional driving workload, which adversely affects the driver's performance [48].…”
Section: Effect Of Curve Radius On Speed Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…A sharp horizontal curve leads to the maximum difference in operating speed if the AT speed is high. Radii of horizontal alignment less than 100 m have a significant influence on speed [47]. Furthermore, the driving workload is primarily generated during the maneuver stage, and a radius of horizontal alignment of less than 500 m imposes an additional driving workload, which adversely affects the driver's performance [48].…”
Section: Effect Of Curve Radius On Speed Behaviormentioning
confidence: 99%
“…The results of the study also confirm that a radius ≤500 m significantly affects vehicle speed. Several researchers have found that a sharp horizontal alignment is a significant contributor to differences in speed between tangent and curve sections [33,47].…”
Section: Effect Of Curve Radius On Speed Behaviormentioning
confidence: 99%